2020
DOI: 10.1097/aln.0000000000003063
|View full text |Cite|
|
Sign up to set email alerts
|

Preoperative Risk and the Association between Hypotension and Postoperative Acute Kidney Injury

Abstract: Background Despite the significant healthcare impact of acute kidney injury, little is known regarding prevention. Single-center data have implicated hypotension in developing postoperative acute kidney injury. The generalizability of this finding and the interaction between hypotension and baseline patient disease burden remain unknown. The authors sought to determine whether the association between intraoperative hypotension and acute kidney injury varies by preoperative risk. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
141
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(170 citation statements)
references
References 50 publications
4
141
1
1
Order By: Relevance
“…The incidence was similar to that recently published in data by Nishimoto [15] (6%, non-cardiac surgery; mean age, 63 years). In our study, the univariable analysis identi ed male sex, smoking, alcohol consumption, anemia, hypertension, diabetes mellitus, ACEI use, CCB use, diuretic use, eGFR, ASA grade III-V, no general anesthesia, emergency, surgical grade 4, duration of the operation (> 120 min), transfusion (> 100 mL), and hemorrhage (> 600 mL) to be associated with AKI, which are similar to previously published data [16,17].…”
Section: Discussionsupporting
confidence: 88%
“…The incidence was similar to that recently published in data by Nishimoto [15] (6%, non-cardiac surgery; mean age, 63 years). In our study, the univariable analysis identi ed male sex, smoking, alcohol consumption, anemia, hypertension, diabetes mellitus, ACEI use, CCB use, diuretic use, eGFR, ASA grade III-V, no general anesthesia, emergency, surgical grade 4, duration of the operation (> 120 min), transfusion (> 100 mL), and hemorrhage (> 600 mL) to be associated with AKI, which are similar to previously published data [16,17].…”
Section: Discussionsupporting
confidence: 88%
“…MAP at admission has been identified as a risk factor for ICU mortality and indicator of kidney perfusion [8,17] . Computed ROC analysis showed an optimal aMAP cut-off value of 79.4 mmHg for the prediction of in-hospital death in PE patients (specificity 0.805,sensitivity 0.600,AUROC 0.729).Current guidelines recommend targeting a MAP ≥ 65 mmHg in septic patients [18] .But the optimal MAP remains an area of debate.In this study,we found that optimal aMAP for patients with PE was 80-90 mmHg.In group 4 and group5,four patients died in hospital(2 received vasopressor therapy,1 with uncontrolled hypertension).It seems that keeping aMAP ≥ 90 mmHg would not benefit PE patients.It has been proved out that higher MAP was detrimental to patients,especially to patients without hypertension [19,20] .Too much dose of vasopressors like norepinephrine and dobutamine, may contribute to higher MAP level.Excessive vasoconstriction may deteriorate tissue perfusion and trigger or aggravate arrhythmias [21] .Vasopressors could increase RV inotropy and systemic BP,promote positive ventricular,interactions lowers filling pressures [3] ,however,raising the cardiac output may aggravate the ventilation/perfusion mismatch by further redistributing flow from(partly) occluded to unoccupied artery [22] .Uncontrolled hypertension could increased left ventricular after-load.…”
Section: Discussionmentioning
confidence: 99%
“…MAP at admission has been identified as a risk factor for ICU mortality and an indicator of kidney perfusion [8,17] . Computed ROC analysis showed an optimal aMAP cut-off value of 79.4 mmHg for the prediction of in-hospital death in PE patients (specificity 0.805, sensitivity 0.600, AUROC 0.729).…”
Section: Discussionmentioning
confidence: 99%